Shank2 Mutant Mice Display Hyperactivity Insensitive to Methylphenidate and Reduced Flexibility in Social Motivation, but Normal Social Recognition - Ey, Elodie; Torquet, Nicolas; de Chaumont, Fabrice; Lévi-Strauss, Julie; Ferhat, Allain-Thibeault; Le Sourd, Anne-Marie; Boeckers, Tobias M.; Bourgeron, Thomas (Frontiers in Molecular Neuroscience, 2018)
Mouse models of autism can be used to study evolutionarily conserved mechanisms underlying behavioral abnormalities in social communication and repetitive behaviors. SHANK genes code for synaptic scaffolding proteins at excitatory synapses and mutations in all SHANK genes have been associated with autism. Here, we present three behavioral aspects of the mutant mice deleted for exon 16 in Shank2. First, we treated Shank2 mutant mice with methylphenidate to rescue the hyperactivity. Our failure to do so suggests that the hyperactivity displayed by Shank2 mutant mice is not related to the one displayed by the typical mouse models of hyperactivity, and might be more closely related to manic-like behaviors. Second, by testing the effect of group housing and social isolation on social interest, we highlighted that Shank2 mutant mice lack the typical flexibility to modulate social interest, in comparison with wild-type littermates. Finally, we established a new protocol to test for social recognition in a social context. We used this protocol to show that Shank2 mutant mice were able to discriminate familiar and unknown conspecifics in free interactions. Altogether, these studies shed some light on specific aspects of the behavioral defects displayed by the Shank2 mouse model. Such information could be used to orient therapeutic strategies and to design more specific tests to characterize the complex behavior of mouse models of autism.